Experimental and numerical static tests of tensegrity triplex modules - Rutkiewicz, Andrzej; Małyszko, Leszek (Bulletin of the Polish Academy of Sciences Technical Sciences, 2024)
The paper presents chosen results of experimental tests performed on physical mock-ups of tensegrity triplex modules, approximately 1.2 m tall and of 0.5 m diameter, made of steel. A uniform and uniaxial static compressive loading is applied to three upper nodes of the modules at six different self-stress levels. Cable forces are measured using specially crafted force transducers of an electro-resistive strain-gauge type. Two types of struts with different slenderness are incorporated to analyze the influence of buckling on the behaviour of the modules. A simple three-parameter mathematical model is presented to explain the behaviour of the modules and discuss the obtained experimental data. The results show nonlinear behaviour in the equilibrium path, as well as, rapidly decreasing axial stiffness in the post-critical phase. An increase in prestress has a small influence on the stiffness in the chosen range of compressive loading. The experimental results are valuable for purposes of verification and validation of numerical studies and fill the lack of experimental data in the literature.